2013
DOI: 10.1111/jce.12123
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Cardioverter Defibrillators in Patients with Cardiac Amyloidosis

Abstract: A high rate of appropriate ICD shocks was observed especially in patients with AL-type amyloidosis. However, appropriate ICD therapy did not translate into overall survival benefit, suggesting that selection of patients with CA who might be candidates for ICD is imprecise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 166 publications
(115 citation statements)
references
References 25 publications
1
108
0
6
Order By: Relevance
“…Another report suggested a benefit of an implantable cardioverter defibrillator (ICD) in a subset of patients with a history of sustained and/or nonsustained ventricular tachycardia [143], but lacked a comparator arm. Our experience suggests that despite appropriate shock delivery, lack of a survival benefit for ICD implantation indicates a difficulty in appropriate patient selection [144]. Identification of indications for ICD installation await collaborative trials.…”
Section: Treatmentmentioning
confidence: 99%
“…Another report suggested a benefit of an implantable cardioverter defibrillator (ICD) in a subset of patients with a history of sustained and/or nonsustained ventricular tachycardia [143], but lacked a comparator arm. Our experience suggests that despite appropriate shock delivery, lack of a survival benefit for ICD implantation indicates a difficulty in appropriate patient selection [144]. Identification of indications for ICD installation await collaborative trials.…”
Section: Treatmentmentioning
confidence: 99%
“…[179][180][181][182] Although appropriate implantable cardioverter defibrillator device therapy has been observed in patients with AL cardiac amyloid, studies to date have not demonstrated a survival advantage. 183 A study of implanted cardiac rhythm recorders found that sudden death in AL amyloidosis is commonly due to pulseless electrical activity, often preceded by bradycardia. 184 Given the absence of randomized studies, the role of implantable cardioverter defibrillator therapy for primary prevention in cardiac AL amyloidosis remains unclear.…”
Section: Grade Of Recommendation Cmentioning
confidence: 99%
“…3 Studies have not shown any survival benefit from implantable defibrillators, 4,5 and no studies have yet examined the benefit of biventricular pacing.…”
Section: Lessonmentioning
confidence: 99%